2011
DOI: 10.1111/j.1582-4934.2010.01165.x
|View full text |Cite
|
Sign up to set email alerts
|

Butyrylcholinesterase interactions with amylin may protect pancreatic cells in metabolic syndrome

Abstract: The metabolic syndrome (MetS) is a risk factor for type 2 diabetes mellitus (T2DM). However, the mechanisms underlying the transition from MetS to T2DM are unknown. Our goal was to study the potential contribution of butyrylcholinesterase (BChE) to this process. We first determined the hydrolytic activity of BChE in serum from MetS, T2DM and healthy individuals. The ‘Kalow’ variant of BChE (BChE-K), which has been proposed to be a risk factor for T2DM, was genotyped in the last two groups. Our results show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 53 publications
2
5
0
Order By: Relevance
“…Additionally, we did not measure other variables associated with parasympathetic activity such as heart rate variability or heart rate values. However, we demonstrated the close correlation between our biomarkers and parallel physiological variables in past studies (21,22). And lastly, Figure 6 represents the current knowledge about the two cholinesterases (AChE and BChE) and their contribution to the cholinergic status and its effect on the heart and inflammatory profile of MACE patients.…”
Section: Limitationssupporting
confidence: 73%
See 2 more Smart Citations
“…Additionally, we did not measure other variables associated with parasympathetic activity such as heart rate variability or heart rate values. However, we demonstrated the close correlation between our biomarkers and parallel physiological variables in past studies (21,22). And lastly, Figure 6 represents the current knowledge about the two cholinesterases (AChE and BChE) and their contribution to the cholinergic status and its effect on the heart and inflammatory profile of MACE patients.…”
Section: Limitationssupporting
confidence: 73%
“…In past studies, we demonstrated the close correlation between our biomarkers and parallel physiological variables such as resting and recovery heart rate after stress testing (21,22,36).…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…None of the patients included in our study suffered an ischemic stroke; nevertheless, our results support a hypothesis of a tight correlation between cholinergic activity and the inflammatory response. Inversely, patients with metabolic syndrome have been shown to express increased BChE activities, such that reductions in their BChE might be masked [ 38 ]. The BChE activity was not measured prior to inflammation; therefore, we cannot exclude the possibility that patients with metabolic syndrome might show false elevated BChE activity levels during the systemic inflammatory disease.…”
Section: Discussionmentioning
confidence: 99%
“…For example, BChE was found to have aryl acylamidase activity and was pro posed to attenuate amyloid plaque formation and contrib ute to neurogenesis. In this respect, the K variant of BChE shows weakened protein interactions and lower stability and hydrolytic activity, in spite of an intact active site (Podoly et al, 2009;ShenharTsarfaty et al, 2011).…”
Section: Nonclassical Cholinesterase Functionsmentioning
confidence: 95%